Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan dan Free Cash Flow Terhadap Manajemen Laba - Febriyanti Febriyanti; Indawati Indawati (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
Earnings management is an effort undertaken by company management to influence financial statement information to achieve specific objectives. Therefore, this study aims to examine and analyze the influence of Tax Planning, Deferred Tax Expense, and Free Cash Flow on Earnings Management. This research is quantitative, using secondary data. The data analysis method used is panel data regression using Microsoft Excel and Eviews 12. The population in this study was all non-cyclical customer sectors listed on the Indonesia Stock Exchange from 2019 to 2023. The data collection technique used was purposive sampling, resulting in 14 samples from the 130-person population processed in this study. The results indicate that Tax Planning, Deferred Tax Expense, and Free Cash Flow simultaneously influence Earnings Management in non-cyclical customer companies from 2019 to 2023. While partially, Tax Planning influences Earnings Management, Deferred Tax Expense Influences Earnings Management, and Free Cash Flow does not.